Employee Performance Analysis In KPRI-Korps Health Employees In Sumedang - Sumiyati , Ai Sri; Henriawan, Desan (SINTESA, 2023)
The focus of this research is to analyze employee performance at the KPRI-Sumedang Health Employee Corps (KPKS). This research aims to determine employee performance, determine the factors that hinder employee performance at the KPRI-Sumedang Health Employee Corps (KPKS) and the efforts made to overcome obstacles to employee performance at the KPRI-Sumedang Health Employee Corps (KPKS). The method used in this research is qualitative method. Research data uses the Miles and Huberman model, activities in data analysis which include data collection, data reduction, data presentation, and drawing conclusions. The research results show that the performance of employees at the KPRISumedang Civil Service Corps (KPKS) has been carried out well, in terms of quantity, cost reduction, and relationships between employees. However, quality, time and supervision are still not optimal, because there are still several obstacles in completing the work. And the efforts made to overcome obstacles to employee performance include increasing accuracy and thoroughness to minimize errors in completing work, improving work discipline and increasing supervision for employees who arrive late by providing sanctions or warnings. Based on the results of the analysis, it can be concluded that the performance of employees at the KPRI- Sumedang Health Employee Corps has not completely gone well according tothe indicator stages according to Kasmir (2020).